The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1600-051x.2007.01048.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smoking on serum RANKL and OPG in sex, age and clinically matched supportive‐therapy periodontitis patients

Abstract: Bone loss in smoker-related periodontitis patients may be partially explained by suppression of OPG production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
70
2
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 40 publications
9
70
2
4
Order By: Relevance
“…Looking at the younger subgroup (20-29y), who had the lower 25(OH)D levels, we did not find any differences in the indices of bone remodeling between smokers and non-smokers, although smoking has been associated with reduced OPG production and increased bone remodeling, as shown by Lappin et al 33 In terms of the routine measurements of calcium, phosphate, ALP and PTH, studies have demonstrated that these parameters are not adequate to identify patients with hypovitaminosis D 7,32 and are thus not reliable predictors of hypovitaminosis D. 31 Studies of the relationship between vitamin D status and bone turnover have yielded conflicting results, 7,34-36 which may be attributed, at least in part, to differences in dietary calcium intake. Notably, several studies supported an inverse relationship between 25(OH)D and serum PTH (and consequently bone turnover markers as a result of secondary hyperparathyroidism) when dietary Ca intake is adequate; 37,38 it should be noted that in our study, the daily dietary calcium consumption was very low (on average 328mg/day).…”
Section: Resultssupporting
confidence: 49%
“…Looking at the younger subgroup (20-29y), who had the lower 25(OH)D levels, we did not find any differences in the indices of bone remodeling between smokers and non-smokers, although smoking has been associated with reduced OPG production and increased bone remodeling, as shown by Lappin et al 33 In terms of the routine measurements of calcium, phosphate, ALP and PTH, studies have demonstrated that these parameters are not adequate to identify patients with hypovitaminosis D 7,32 and are thus not reliable predictors of hypovitaminosis D. 31 Studies of the relationship between vitamin D status and bone turnover have yielded conflicting results, 7,34-36 which may be attributed, at least in part, to differences in dietary calcium intake. Notably, several studies supported an inverse relationship between 25(OH)D and serum PTH (and consequently bone turnover markers as a result of secondary hyperparathyroidism) when dietary Ca intake is adequate; 37,38 it should be noted that in our study, the daily dietary calcium consumption was very low (on average 328mg/day).…”
Section: Resultssupporting
confidence: 49%
“…Apatzidou et al (2005) stated that smokers with periodontal disease have a suppressed inflammatory response, a significantly less favourable clinical outcome and seem to have an altered host antibody response to antigenic challenge than non-smokers although; the subgingival microflora of smokers appears similar to that of non-smokers. Lappin et al (2007) reported decreased serum OPG levels and greater soluble receptor activator of nuclear-factor kappa B ligand (sRANKL) sRANKL/OPG ratios in smoker patients in the maintenance program than the non-smoker counterparts. Negative correlation between pack-years and total OPG amount in peri-implant crevicular fluid was detected in clinically healthy implants (Arıkan et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with diagnosed periodontitis have been reported to have an increase in RANKL and a decrease in OPG in both the gingival tissues and in gingival crevicular fluid. As a consequence, RANKL/OPG ratios are found to be increased in periodontitis patients when compared to healthy controls (Buduneli et al 2008;Lappin et al 2007;Tang et al 2009). …”
Section: Periodontitis In Smokersmentioning
confidence: 97%
“…Periodontitis is a chronic inflammatory disease that is caused by an infection of anaerobic, gram-negative bacteria (Buduneli et al 2008;Lappin et al 2007). The bacteria colonize in the subgingival area, and they cause localized and systemic elevations of pro-inflammatory cytokines (Buduneli et al 2008).…”
Section: Periodontitis In Smokersmentioning
confidence: 99%
See 1 more Smart Citation